2004
DOI: 10.1007/s11998-004-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of polyurethane dispersions in a batch rotor-stator mixer

Abstract: In this study, the effect of high energy input from mechanical agitation, provided with a high shear rotor-stator, on the drop size and the drop size distribution (DSD) of aqueous polyurethane (PU) dispersions is investigated. The effect of the dispersed phase volume fraction (φ) on the DSD of aqueous PU dispersions is also examined to understand the fundamental characteristics that result from the high shear mixing. DSD is measured by using either a high magnification video probe or dynamic light scattering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…This is partly in agreement with the findings of Phongikaroon et al, who indicated that mechanical stirring does not influence the mean particle size for PU dispersions. 4 Contrary to their findings, the current results also indicate that rotational speed does not affect the polydispersity. However, the particle sizes obtained in this study are 2 orders of magnitude smaller than the particles obtained by Phongicaroon, Calabrese, and Carpenter, and these PU dispersions are UV-PUDs.…”
Section: ■ Materials and Methodscontrasting
confidence: 99%
See 3 more Smart Citations
“…This is partly in agreement with the findings of Phongikaroon et al, who indicated that mechanical stirring does not influence the mean particle size for PU dispersions. 4 Contrary to their findings, the current results also indicate that rotational speed does not affect the polydispersity. However, the particle sizes obtained in this study are 2 orders of magnitude smaller than the particles obtained by Phongicaroon, Calabrese, and Carpenter, and these PU dispersions are UV-PUDs.…”
Section: ■ Materials and Methodscontrasting
confidence: 99%
“…However, rotor-stator mixers (RSMs) are also expected to have a significantly higher mixing intensity than the batch stirrer; therefore, it is not necessarily the processing mode (batch or continuous) that resulted in the reduced particle size and increased stability. Phongicaroon, Calabrese, and Carpenter investigated PU dispersions in a batch RSM and showed that the mechanical agitation was mainly responsible for the width of the particle size distribution . Increasing the rotational speed reduced the width of the distribution but not the mean diameter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to emulsion processing where energy plots are commonly used to directly compare measured volumetric energy input or energy dissipation rates and resulting mean bubble size (e.g. Davies, 1985;Karbstein & Schubert, 1995;Schrö der, 1999;Phongikaroon, Calabrese, & Carpenter, 2004;Lambrich & Schubert, 2005), no such publications were found for foams. The energy dissipation rate (=volumetric power input) focuses on the acting stresses only and disregards time dependency.…”
Section: E [J/m ]mentioning
confidence: 99%